Characterization of nucleolin K88 acetylation defines a new pool of nucleolin colocalizing with pre‐mRNA splicing factors. Issue 5 (24th January 2013) - Das, Sadhan; Cong, Rong; Shandilya, Jayasha; Senapati, Parijat; Moindrot, Benoit; Monier, Karine; Delage, Hélène; Mongelard, Fabien; Kumar, Sanjeev; Kundu, Tapas K.; Bouvet, Philippe
Abstract : Nucleolin and SC35 colocalize by fluorescence microscopy (View interaction) Abstract : ► Nucleolin is acetylated in vivo. ► Antibody specific for nucleolin acetylation was developed. ► Acetylated nucleolin is present in nucleoplasmic speckles. ► Acetylated nucleolin co‐localizes with splicing factor SC35.